The «procedural autonomy» and the Constitutional Court: notes on an invented relationship - Monroy Gálvez, Juan (2007)
The author deals with the background of what is known as the institute of «procedural autonomy»; to this end he employs the study made by the Spanish author Patricia Rodríguez-Mendoza and concludes that the study does not, in fact, deal with «procedural autonomy» (proceeding) but rather «procedural autonomy». Finally, the author concludes that with his article he looks to reveal that the use of the Constitutional Procedural Autonomy has been the foundation for the harmful effects caused in various verdict of the Constitutional Court.